Do marriage markets influence the divorce hazard? - Raphaela Hyee (Queen Mary University of London, School of Economics and Finance, 2011)
This paper demonstrates that a woman's propensity to separate from her husband or live-in partner depends positively on male wage inequality on her local marriage market - the more heterogeneous potential future mates are in terms of earnings power, the more likely a woman is to end her relationship. This effect is strongest for couples, were one has a college education but the other one does not. Because of the high degree of assortative matching according to education on the marriage market, college educated individuals are those most likely to marry a college graduate - if they are not currently married to one, they have the most to gain from divorcing and going back to the marriage market. This incentive becomes stronger if the college premium (the wage advantage college graduates enjoy over non-graduates) rises. The effect is robust to the inclusion of a variety of controls on the individual level, as well as state and time fixed effects and state specific time trends.
Keywords: J12; J31; D31; I24; 330; education; inequality; divorce